"The Message Is You Don't Exist": Exploring Lived Experiences of Rural Lesbian, Gay, Bisexual, Transgender, Queer/Questioning (LGBTQ) People Utilizing Health care Services. (September 2021) - Henriquez, Nadine R.; Ahmad, Nora
Background: Lesbian, gay, bisexual, transgender, queer/questioning (LGBTQ) people experience significant health inequities with well-documented negative health impacts due to their status as a sexual and gender minority population. Insensitive or discriminatory attitudes toward LGBTQ people within the health care system have negatively impacted access to health services and the overall physical and mental health and well-being of this at risk population. Few studies of LGBTQ populations in rural areas have been conducted, with even fewer in the Canadian context. Rural areas often create greater visibility for LGBTQ persons, contain fewer supports and alternatives in the face of discrimination, and are often are less accepting of LGBTQ populations due to increased stigma and social isolation. Objective: The purpose of this study is to examine the lived experiences of LGBTQ people utilizing health care services in rural Manitoba. Method: 12 individuals who self-identified as LGBTQ who had accessed health care services in Manitoba were recruited. Using qualitative methodology, interviews were recorded and analyzed for themes. Results: Analysis revealed themes including stigma and discrimination, judgments and assumptions, gender identities, lack of knowledge, limited access/systemic barriers, rural considerations, and recommendations for changes to address the gaps in health care services and barriers to access. Conclusions: This study of the LGBTQ community provides an expression of their opinions and experiences, but also provides a voice to this underserved population. The findings of this study provide a better understanding of the unique health needs and experiences of LGBTQ people in rural Manitoba, creating opportunities for meaningful change in health care delivery